Bacterial Associations Across House Fly Life History: Evidence for Transstadial Carriage From Managed Manure. Issue 1 (21st January 2016) - Zurek, Klara; Nayduch, Dana
Abstract: House flies (Diptera: Muscidae; Musca domestica L.) associate with microbe-rich substrates throughout life history. Because larvae utilize bacteria as a food source, most taxa present in the larval substrate, e.g., manure, are digested or degraded. However, some species survive and are present as third-instar larvae begin pupation. During metamorphosis, many bacteria are again lost during histolysis of the larval gut and subsequent remodeling to produce the gut of the imago. It has been previously demonstrated that some bacterial species survive metamorphosis, being left behind in the puparium, present on the body surface, or in the gut of the emerged adult. We used a combined culture-molecular approach to identify viable microbes from managed manure residue and a wild population of house fly larvae, pupae, puparia, and adults to assess transstadial carriage. All larval (10/10), pupal (10/10), and puparial (10/10) cultures were positive for bacteria. Several bacterial species that were present in larvae also were present either in pupae or puparia. Four viable bacterial species were detectable in 6 of 10 imagoes reared from manure. Of note is the apparent transstadial carriage of Bacillus sonorensis, which has been associated with milk spoilage at dairies, and Alcaligenes faecalis, which can harbor numerous antibiotic resistance genes on farms. The potential of newly emerged flies to harbor and disseminate bacteria from managed manure on farms is an understudied risk that deserves further evaluation.